Manifestations of Critical Realism in George Bernard Shaw's Critical Works (Journal of Hama University, 2019)
This research attempts to uncover the extent to which the factual and critical stance of the world playwright George Bernard Shaw and his critical works when he worked as a technical critic in some magazines and newspapers in the prime of his literary career.For this purpose, Bernard Shaw's critique of Bernard Shaw's critical factual position in his work in musical criticism is based on Bernard Shaw's preference for musician Richard Wagner for other musicians because he mixes thought with art and creates realistic operas.Bernard Shaw's critique of Shakespeare's plays, a critique of a violent attack on the Shakespearen themes of the play, it is not a matter of living reality, but from Bernard Shaw's critical point of view, a mixture of mythological, emotional and fictional fantasies.Bernard Shaw's critical view of the real Henrik Ibsen theater, and the extent to which Bernard Shaw celebrates this theater, appreciates and glorifies it, is a realistic theater that tackles realist themes and monitors society's problems and evils in a highly critical and critical spirit. It makes you re-create reality on stage.Then, the research concludes showing the extent to which Bernard Shaw's critical works have been established and his realistic and critical stance by Bernard Shaw in his critique of every artistic and literary work, making it the benchmark in his critical works, which has become a self- critical work.